Antecedents and outcomes of employees’ attitude towards corporate social responsibility in a private university - Gunasagaran, Krishneswari (2018)
The purpose of this study is to examine the antecedents and outcomes of employees‟ attitude towards Corporate Social Responsibility in a Private University. Corporate Social Responsibility (CSR) has been widely studied in the literature where many of theories focused on CSR effect on individual and organisational outcomes. Understanding employee‟s CSR attitude is important for organisation to structure its CSR program. However, research that investigates factors influencing employee‟s CSR attitude is scarce. This study investigated a Private University‟s Corporate Social Responsibility (CSR) structures and their influences on employee‟s attitude towards CSR activities. Moreover, this study explored the effect of altruism as moderating variable. This study used the quantitative method by distributing questionnaires to employees of a private university that made CSR participation as one of the employees‟ Key Performance Indicator (KPI). There were 358 questionnaires collected from the employees of the private university. This study uses a purposive sampling where judgement imposed was the employee must worked for more than one year. Furthermore, Social Identity Theory (SIT) and Theory Planned Behaviour (TPB) were applied in supporting the proposed sixteen relationships and hypotheses. Partial Least Square Structural Equation Modeling (PLS-SEM 3.0) was used to analyse data. The results of this study showed that nine out of sixteen hypotheses were supported. CSR recognition and altruism were found to be significant with attitude towards CSR. Besides that, attitude towards CSR was found to be positively related to participation intention. Participation intention positively related to organisational identification which was positively related to employee commitment. Also, altruism as moderator was significant for CSR compulsion, CSR association and CSR recognition, on attitudes towards CSR. Some implications were derived from this study. First, organisations should be aware of the impact of CSR recognition have on employee attitude towards CSR. It is beneficial for organisation to lay out effective CSR recognition program that may attract, motivate and improve employee attitude towards CSR. Second, organisation are suggested to practice flexible KPI where employees who are altruistic are allowed to allocate more weighting score on CSR activities they like to get involved in. Hence, it helps the employees to voluntarily participate in CSR activities according to their personal value profile.